Interleukin-35 Attenuates D-Galactosamine/Lipopolysaccharide-Induced Liver Injury via Enhancing Interleukin-10 Production in Kupffer Cells - Zheng, Xing-Feng; Hu, Xiao-Yan; Ma, Bing; Fang, He; Zhang, Fang; Mao, Yan-Fei; Yang, Feng-Yong; Xiao, Shi-Chu; Xia, Zhao-Fan (Frontiers in Pharmacology, 2018)
Interleukin (IL) -35 is an anti-inflammatory cytokine which exerts various beneficial effects on autoimmune diseases. However, whether IL-35 plays a role in endotoxin induced hepatitis demands clarification. This study aims to reveal the effect and mechanism of IL-35 on endotoxin induced liver injury. Acute hepatic injury was induced by D-galactosamine (D-GalN, 400 mg/kg) and lipopolysaccharide (LPS, 5 μg/kg) administration in mice. IL-35 treatment ameliorated D-GalN/LPS induced liver injury in a dose dependent manner as shown by histological examination, ALT determination and Caspase-3 activity assay. It also reduced production of pro-inflammatory cytokines, tumor necrosis factor (TNF)-α, IL-1β and IL-6, and increased production of anti-inflammatory cytokines, IL-4, IL-10 and transforming growth factor (TGF)-β. This hepato-protective effect was proved mainly mediated by Kupffer cells (KC) via gadolinium chloride depletion and cell adoptive transfer experiment. In addition, IL-35 emolliated the cytotoxicity of LPS-triggered KCs to hepatocytes, suppressed nitric oxide (NO) and TNF-α production, and elevated IL-10 production in LPS stimulated KCs. Furthermore, IL-35 could not exert hepato-protective effect in IL-10-deficient mice in vivo and it could not suppress LPS induced NO and TNF-α production in IL-10-deficient KCs in vitro. In conclusion, IL-35 protects endotoxin-induced acute liver injury, which mainly acts thought increasing IL-10 production in KCs. This finding demonstrates a role of IL-35 in anti-infectious immunity and provides a potential therapeutic target in treating fulminant hepatitis.